Useful autosomal STR marker sets for forensic and paternity applications in the Central Indian population - Hirak Ranjan Dash; Neha Rawat; Kamayani Vajpayee; Pankaj Shrivastava; Surajit Das (Taylor & Francis Group, 2021)
Background Many countries have developed their core set of STR loci for forensic application and database generation, which India lacks. Aim To assess the usefulness of various combinations of autosomal STR marker sets for their superior use in the central Indian population for forensic and paternity applications. Subjects and methods 19 STR marker sets were analysed on 200 central Indian populations and 20 paternity cases to assess their usefulness. Results Two marker sets each comprising 19 STR markers are found to be superior to 20 expanded CODIS loci in the studied population. These marker sets also showed their effectiveness in 20 paternity cases having CPI values of 7.62 × 1011 and 7.16 × 1011. Three non-CODIS STR markers Penta E, Penta D, and SE33 showed amplification in 50 challenging samples with >0.80 heterozygosity. Conclusion Population-specific STR marker sets are useful in forensic and paternity applications, as well as database generation, and it is envisioned that Penta E, Penta D, and SE33 markers will be included in the list of core STR loci in the central Indian population.